DEVELOPMENT OF E-BOOKS AS TEACHING MATERIALS IN THE COMPUTER AND NETWORK ENGINEERING DEPARTMENT - Karurukan, Desnal Galla; Hasni, Hasni; Ervianti, Ervianti (Indonesian Journal of Educational Technology, 2024)
Makale Christian Vocational School faces learning difficulties due to the ineffective use of textbooks, making it difficult for students to understand the material. Therefore, it is necessary to develop e-books as a learning medium to increase students' understanding in the Basic Computer and Network subjects for class X TKJ. This research aims to: (1) analyze the need for developing e-books as teaching materials, (2) design an e-book development design, and (3) describe the level of validation and practicality of the e-book. The method used is Research and Development with the ADDIE model, including analysis of student characteristics, school environment and curriculum. The design stage includes creating a storyboard and compiling content, while the development stage includes media validation and practicality testing. This research was conducted at Makale Christian Vocational School with the subject of class X students and involved validators, students and teachers. The research results show that this e-book is very feasible, with a media validator assessment of 80%, material validator assessment of 90%, teacher assessment of 86%, and student assessment of 94%.